2013
DOI: 10.1103/physreve.87.012202
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the feeding mechanism on deposits of square particles

Abstract: In a previous paper [Hidalgo et al., Phys. Rev. Lett. 103, 118001 (2009)] it was shown that square particles deposited in a silo tend to align with a diagonal parallel to the gravity, giving rise to a deposit with very particular properties. Here we explore, both experimentally and numerically, the effect on these properties of the filling mechanism. In particular, we modify the volume fraction of the initial configuration from which the grains are deposited. Starting from a very dilute case, increasing the vo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
10
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 43 publications
3
10
0
Order By: Relevance
“…When the column is built with a higher feeding rate, however, the polar distribution of the principal direction is more uniform, denoting the establishment of a more spherical stress state. For very high feeding rate, however, this effect is reversed (data not shown) in accord with the non monotonic behavior displayed in Fig.3a [17].…”
Section: Micromechanicssupporting
confidence: 71%
See 1 more Smart Citation
“…When the column is built with a higher feeding rate, however, the polar distribution of the principal direction is more uniform, denoting the establishment of a more spherical stress state. For very high feeding rate, however, this effect is reversed (data not shown) in accord with the non monotonic behavior displayed in Fig.3a [17].…”
Section: Micromechanicssupporting
confidence: 71%
“…Moreover we will express our results in terms of a dimensionalized feeding rate f * = f /W = vφ 0 /A. More details about the experimental setup can be found in [17].…”
Section: Methodsmentioning
confidence: 99%
“…The increase of these interactions has also been observed in experiments [42] as well as in numerical simulations with elongated particles in 2D [15,18].…”
Section: Summary and Discussionsupporting
confidence: 48%
“…The computational time is further reduced using a combination of the Verlet distance concept and neighbor tables that is tailored for this particular case of geometrical objects [43][44][45][46]. While the major application of this method has been the investigation of granular flow [47] and pedestrian flow [48], it is shown that particles generated by Minkowski sums are promising in the investigation of the effects of friction and rheology due in flat and nonconvex particles [49,50]. Here we exploit further the effect of nonconvexity on friction by using nonconvex spheropolygons with complex (fractal) topography.…”
Section: Spheropolygon-based Simulations Of Friction Between Fracmentioning
confidence: 99%